2012
DOI: 10.1186/1743-8977-9-38
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of cardiac ischemia/reperfusion injury after instillation of three forms of multi-walled carbon nanotubes

Abstract: BackgroundThe exceptional physical-chemical properties of carbon nanotubes have lead to their use in diverse commercial and biomedical applications. However, their utilization has raised concerns about human exposure that may predispose individuals to adverse health risks. The present study investigated the susceptibility to cardiac ischemic injury following a single exposure to various forms of multi-walled carbon nanotubes (MWCNTs). It was hypothesized that oropharyngeal aspiration of MWCNTs exacerbates myoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 72 publications
7
30
0
Order By: Relevance
“…For example, our earlier studies found that MWCNTs with a length of 10-100 μm impaired pulmonary function 22 and induced severe cardiac ischemic/ reperfusion injury after pulmonary instillation. 23 Similar results on MWCNT toxicity were also reported elsewhere, [24][25][26][27] such as subchronic toxicity, asbestos-like pathogenicity in mice, and airway fibrosis. In contrast, CNTs with a length shorter than 2 μm have been shown to exhibit minimal toxicity to various cell types, such as human promyelocytic leukemia (HL60) and human T-cells (Jurkat).…”
supporting
confidence: 83%
“…For example, our earlier studies found that MWCNTs with a length of 10-100 μm impaired pulmonary function 22 and induced severe cardiac ischemic/ reperfusion injury after pulmonary instillation. 23 Similar results on MWCNT toxicity were also reported elsewhere, [24][25][26][27] such as subchronic toxicity, asbestos-like pathogenicity in mice, and airway fibrosis. In contrast, CNTs with a length shorter than 2 μm have been shown to exhibit minimal toxicity to various cell types, such as human promyelocytic leukemia (HL60) and human T-cells (Jurkat).…”
supporting
confidence: 83%
“…[558]. However, Urankar et al [757] suggested that oropharyngeal aspiration of MWCNT, especially MWNCNTs, produced the greatest expansion of the infarct. The authors suggested that the effect is dependent on the dose and the form of MWCNTs but concluded that, in general, the presence of MWCNTs may pose a significant risk to the cardiovascular system.…”
Section: Internalization Of Functionalized Cnts Into Cells Was Recentmentioning
confidence: 99%
“…11−13 For CNTs, Urankar et al reported that oropharyngeal aspiration of MWCNTs resulted in a time and dose-dependent exacerbation of myocardial infarction when assessed at days 1, 7, and 30 postaspiration. 14 The severity of myocardial injury depended on the form of MWCNTs used. Instillation of SWCNTs in Wistar-Kyoto (WKY) rats was found to alter baroreflex function by affecting cardiovascular autonomic regulation thus contributing to cardiac and arrhythmic events.…”
Section: ■ Introductionmentioning
confidence: 99%